O gênero Heterothalamus lessing e táxones afins - Deble, Leonardo Paz (2004)
The genus Heterothalamus Lessing and genera allied are studied, as a contribution to the knowledge of south-american flora, especially from Brazil, Argentina and Uruguay. The genus Heterothalamulopsis is a taxonomic novelty. Monotypic until this moment, it is here described, illustrated and commented about its morphological characteristics. Heterothalamulopsis wagenitzii is a dioecious species of small glandulous and ramified shrubs, provided with persistente bristled and broad apex pappus in male flowers, and with ligulate female flowers, protected by persistent paleas. The species, endemic of southern Brazil, occurs only on the border of the “Aparados da Serra Geral”, in the states of Rio Grande do Sul and Santa Catarina. The genus Heterothalamus comprises three polygamo-dioecious or imperfect-dioecious species of small glandulous and ramified shrubs, characterized by the presence of 1-2-series of radial, female or neutral flowers, in functional male heads, and by the presence of ligulate flowers, protected with persistent paleas, in female heads. The geographic distribution of the genus includes central Argentina (Provinces of Cordoba, San Luis, La Rioja and Santiago del Estero), Uruguay and southern Brazil (States of Rio Grande do Sul and Santa Catarina). The three species of Heterothalamus are described and illustrated, beeing their geographic distributions represented in maps. Common names, the botanical synonymity and phenological data are also furnished. It is supplied a key to set apart the genera of subtribe Baccharinae Lessing, found in the brazilian, argentinian and uruguayan floras. Another key is furnisched to distinguish the three studied species of Heterothalamus. In the proposal of the new genus Heterothalamulopsis, it was redescribed the subtribe Baccharinae Lessing. The genera Baccharis L. and Baccharidastrum Cabrera were also redescribed, with the aim to elucidate morphological differences with respect to other studied genera. Baccharis czermackii Hochreutiner was presently reduced to the synonymity of Heterothalamus psiadioides Less.